The effects of Stemregen® host modulation therapy on experimentally induced apical periodontitis in rats - Gonullu, Fatma; Ocak, Mevluet Sinan; Dundar, Serkan; Ozercan, Ibrahim Hanifi (Univ Sao Paulo Fac Odontologia Bauru, 2025)
This study evaluated the effect of Stemregen (R) nutritional supplement on inflammation and resorption in apical periodontitis using a rat model. Methodology: Rats were divided in three groups: negative control (n=7), positive control (n=10), and Stemregen (R) (Stem) (n=10). Apical periodontitis was induced in the positive control and Stem groups, and all rats were sacrificed on the 30th day. Serum phosphorus (P), calcium (Ca), and alkaline phosphatase (ALP) were analyzed. Histopathological assessments measured osteoblastic and osteoclastic activity, inflammation, fibrosis, and abscess density. Immunohistochemical analyses evaluated RANKL, TRAP, and OPG levels. Results: Results showed significantly lower osteoblastic activity in the negative control compared to Stem and positive control groups (p=0.005). Osteoclastic activity was higher in the positive control (p=0.032). Inflammation and abscess formation were reduced in the Stem group compared to the positive control (p<0.001). OPG levels were lower in the negative control compared to the other groups (p=0.005). Conclusion: Stemregen (R) effectively reduced inflammation and bone destruction, suggesting potential benefits for apical periodontitis management, though further research is needed.
Keywords: Apical periodontitis; Stemregen (R); Host modulation; Rat